Характер Василя Стуса як основа психотипу письменника - Пуніна, О.В. (Слово і Час, 2019)
Стаття є логічним продовженням низки міркувань, висловлених у дослідженнях “Наукова
інтерпретація творчої особистості письменника: інтердисциплінарна стратегія”, “Психотип Василя
Стуса: до постановки проблеми”. У цій науковій публікації унаочнено першу частину теоретичної
концепції “психотип – креатор – образ”. Авторка пропонує свій підхід для встановлення
психологічного типу Василя Стуса, виявляє специфіку характеру письменника, на якому завжди
лишають відбиток психічні способи адаптації. Аналіз літературно-побутових матеріалів, що
містять опосередковані спостереження й самоспостереження над характером В. Стуса, дає
змогу виявити особливості психологічної структури індивідуальності на основі багатьох ознак.
Психологічна винятковість поета як цілісності визначена так: самодостатня, інтелектуально
глибока людина сильної волі, схильна до експансивної реакції і в обхід компромісів. Осягнення
морально-вольового, емоційного й інтелектуального складників Стусового характеру наближає
до авторської моделі світоустрою. In the present paper the scholar refers to the first part of her theoretical concept “psychotype –
creator – image” and focuses on the peculiarities of Vasyl Stus’s character. This approach helps to
define the psychological type of the poet. Psychic ways of adaptation always leave a mark on the
character of the individual. The coincidence between indirect observations of friends, acquaintances and
psychological self-characteristics of the writer gives especially important information for the researcher.
The analyzed materials include literary texts and different everyday life records that contain
psychologically mediated observations and self-observations on the character of Vasyl Stus. These data
allow identifying the specific psychological structure of personality based on many characteristics. The
attributes ‘strong-willed’, ‘vulnerable’, ‘sensitive’, ‘quicktempered’, ‘uncompromising’, and ‘intellectual’
may be recognized as key features of this personality. The psychological exclusivity of Vasyl Stus is
presented by the characteristics ‘self-sufficient’, ‘intellectually deep man of strong will’, ‘inclined to
expansive reaction and unsuited for compromise’.
The scrupulous attention to the moral, volitional, emotional and intellectual components of Vasyl
Stus’s character brings the researcher closer to determining the author’s model of the world order.
The defined psychotype of the writer helps to understand the interdependence of the psychological
nature of the author and his literary style.